Trapped between the Dragon and South Asia’s big brother: the case of Sri Lanka’s “balanced” foreign policy - De Silva, Shakthi (Sri Lanka Journal of Social Sciences, 2018)
As China’s influence in the Indian Ocean Region grows in preponderance, Indian anxieties have concomitantly intensified. Faced with finite choices as an island in the Indian Ocean, it is intrinsically in Sri Lanka’s interest to balance both powers. This study examines the escalating strategic competition between India and China in Sri Lanka and unpacks the contours of their activities and their linkages with the island. It assesses the dexterity of the Sirisena administration to actualize a balanced foreign policy in contrast to its predecessor and outlines a policy formulation which would support the government in its endeavor. The article also contributes to the foreign policy strategising literature by configuring four conceivable external dynamics Sri Lanka may face in future.
Keywords: foreign policy; China; India; Sri Lanka; South Asia; Strategic Competition